Notes on taxonomy and distribution of Myrsidea serini (Séguy, 1944) (Phthiraptera: Amblycera: Menoponidae) on Southern South American passerine birds (Aves: Passeriformes) - Cicchino, Armando Conrado (2015)
Myrsidea serini (Séguy, 1944) is recorded from three different passerine hosts from Argentina and Chile: Carduelis barbata (Molina, 1782) (Fringillidae), Chrysomus thilius petersi (Laubmann, 1934) and Agelaioides badius badius (Vieillot, 1819) (Icteridae). Somatic features and body measurements from available specimens belonging to these host-populations are compared with those recorded from Old World hosts, finding only some slight differences in certain body measurements (here interpreted as correlated to differences in host sizes), but none in chaetotaxy. This species was synoxenic with Myrsidea psittaci Carriker, 1955 on C. t. petersi in at least two localities in Buenos Aires Province, Argentina. Comparative studies of external chorionic architecture of the eggs, preferential sites of oviposition, prevalence has been carried out for both species, along with some remarks concerning the still problematic species, Myrsidea argentina (Kellogg, 1906), originally recorded off Carduelis magellanica (Vieillot, 1805).